2015
DOI: 10.1097/xeb.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of audience response system technology on learning outcomes in health students and professionals

Abstract: There is an absence of good quality evidence on effectiveness of ARS technologies for improving learning outcomes in health students and professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Moreover, students stated that teachers were able to track their understanding through use of the ARS. Many studies have confirmed these results (Atlantis and Cheema, 2015;Egelandsdal and Krumsvik, 2017).…”
Section: Formative Feedback From Post-lecture Revision Sessionsmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, students stated that teachers were able to track their understanding through use of the ARS. Many studies have confirmed these results (Atlantis and Cheema, 2015;Egelandsdal and Krumsvik, 2017).…”
Section: Formative Feedback From Post-lecture Revision Sessionsmentioning
confidence: 74%
“…All seven focus groups agreed that post-lecture revision enhanced their understanding, and they particularly praised the explanation and clarification given by the teacher. Similarly, Atlantis and Cheema (2015) reported that the provision of formative feedback and explanation of both correct and incorrect answers by the educator increases students' understanding of the knowledge learned. This improves participants' awareness of their individual learning needs (Atlantis and Cheema, 2015).…”
Section: Formative Feedback From Post-lecture Revision Sessionsmentioning
confidence: 97%
See 1 more Smart Citation
“…One controlled study suggested that immediate feedback after questions (as facilitated by ARS) may improve knowledge condensation [10]. Unfortunately, ARS have shown weak or equivocal results in long-term knowledge retention and learning outcomes; these inconclusive results have impaired academic institutional implementation of the ARS technology [8].…”
Section: Technology In Audience Participationmentioning
confidence: 99%
“…ARS may facilitate student in-classroom participation and encourage group problem solving (depending on how the ARS is integrated into the experience) [8]. Anonymity in responses allows the learner to engage without fear of embarrassment or being singled out by peers or the instructor [9].…”
Section: Technology In Audience Participationmentioning
confidence: 99%